KEBIJAKAN EKONOMI DAN POLITIK INDONESIA MEMILIH BEKERJASAMA DENGAN TIONGKOK DARI PADA JEPANG DALAM PROYEK KERETA CEPAT JAKARTA-BANDUNG TAHUN 2015 - Rahmadoni, Engra; Waluyo, Tri Joko (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research describes the Economic Policy Political Indonesia chose Tiongkok for the development cooperation project High Speed Train Jakarta - Bandung 2015. Previous Tiongkok and Japan are two countries that are eager to invest in Indonesia in the development of this project. Then two countries submitting proposals to Indonesia in order to attract interest in Indonesia to choose one between the two countries to carry out the construction of a High Speed Train project - Jakarta – Bandung. But in the end decided to throw Indonesia to Tiongkok for the construction of this project. The method that is used in this research is qualitative research. Some of the datas are obtained from books, journals, articles,internet and other media. The focus of this research is the reason Indonesia chose to cooperate with Tiongkok in the development of this project , even though Japan is the leading country in the construction of this mass transportation. This study uses a neoliberal perspective and the theory of international cooperation. Indonesia wants to balance the economic influence of China and Japan in the country. Because the amount of investment and international cooperation between the two countries in Indonesia very much value. Japan is a major investor in Indonesia since 1967 and prior to exert influence on the Indonesian economy. For this reason in the end Indonesia chose to cooperate with Tiongkok in this project. In addition, the proposal offered Tiongkok also provide benefits for Indonesia. Indonesia is also a precondition in the development of this fast train and China is willing to run.Keywords: High Speed Train, Investment, International Cooporation